2007
DOI: 10.1038/sj.onc.1210714
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive breast cancer cells are dependent on activated Abl kinases for proliferation, anchorage-independent growth and survival

Abstract: Mutant Abl kinases (such as BCR-Abl) drive the development of leukemia; however little is known regarding whether Abl kinases contribute to the development or progression of solid tumors. We recently demonstrated that endogenous Abl kinases (c-Abl, Arg) are activated by deregulated ErbB receptors and Src kinases, and drive invasion of aggressive breast cancer cells. In this study, we examined whether activation of endogenous Abl kinases affects transformation, proliferation and survival, which are major contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
139
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 30 publications
7
139
0
Order By: Relevance
“…Although this study focused on the apoptotic role of c-Abl, c-Abl is also a pro-proliferative factor (reviewed in Sirvent et al 48 and Colicelli 49 ). Activation of c-Abl in the cytoplasm is involved in the response to growth factors [50][51][52] and F-actin assembly. 53 Furthermore, as shown by the example of CML (chronic myeloid leukemia), uncontrolled activation of ABL is tumorigenic.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study focused on the apoptotic role of c-Abl, c-Abl is also a pro-proliferative factor (reviewed in Sirvent et al 48 and Colicelli 49 ). Activation of c-Abl in the cytoplasm is involved in the response to growth factors [50][51][52] and F-actin assembly. 53 Furthermore, as shown by the example of CML (chronic myeloid leukemia), uncontrolled activation of ABL is tumorigenic.…”
Section: Discussionmentioning
confidence: 99%
“…As unprocessed c-Abl is an approximately 120-kDa protein, this smaller fragment may be explained by cleavage of the protein as demonstrated previously by Machuy et al 29 The finding that ABL1 knockdown resulted in reduced proliferation in both cell lines indicates a functional involvement of c-Abl in the cellular growth of rhabdoid tumor cells in vitro and is well in line with previous findings in extracranial solid tumors, such as breast cancer. [34][35][36] To further evaluate this involvement, we studied blockage of c-Abl signaling by the tyrosine kinase inhibitor imatinib and observed a growth-inhibitory effect against A204 cells and G401 cells that was comparable to the effect observed in breast cancer cell lines that contained highly active c-Abl kinases. 36 Data regarding the efficacy of tyrosine kinase inhibitors like imatinib in rhabdoid tumor cell lines have been controversial: 1 previous study demonstrated that imatinib was effective against the rhabdoid tumor cell line BT12, whereas efficiency against BT16 cells was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] To further evaluate this involvement, we studied blockage of c-Abl signaling by the tyrosine kinase inhibitor imatinib and observed a growth-inhibitory effect against A204 cells and G401 cells that was comparable to the effect observed in breast cancer cell lines that contained highly active c-Abl kinases. 36 Data regarding the efficacy of tyrosine kinase inhibitors like imatinib in rhabdoid tumor cell lines have been controversial: 1 previous study demonstrated that imatinib was effective against the rhabdoid tumor cell line BT12, whereas efficiency against BT16 cells was not observed. 20 It is tempting to speculate that these discrepancies may be related to c-Abl expression.…”
Section: Discussionmentioning
confidence: 99%
“…c-Abl PTK is localized both in the nucleus and in the cytoplasm, and its kinase activity is tightly regulated through different mechanisms (Nagar et al, 2003;Pendergast, 2002;Plattner et al, 1999). Studies suggest that c-Abl and its homolog Arg have important functions in regulating cell proliferation, apoptosis, adhesion, cell migration and stress responses (Yuan et al, 1996(Yuan et al, , 1999Baskaran et al, 1997;Agami et al, 1999;Brasher and Van Etten, 2000;Raina et al, 2006;Srinivasan et al, 2008). The existence of Cterminal DNA-binding motifs and nuclear localization signals in c-Abl enables shuttling between cytoplasmic and nuclear compartments, extending the exposure to additional Abl kinase substrates (Wen et al, 1996;Taagepera et al, 1998;Yoshida et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The activated forms of Abl kinases (BCR-Abl, Tel-Abl and Tel-Arg) induce the development of human leukemia (Skorski et al, 1998;Druker et al, 2001;Pendergast, 2001;Kim et al, 2004). Recent studies suggest that Abl kinases are constitutively activated in breast cancer cells and constitutive activation of Abl kinases promotes breast cancer cell invasion (Srinivasan and Plattner, 2006;Jallal et al, 2007;Srinivasan et al, 2008). Although the mechanism by which BCR-Abl drives leukemiagenesis is well understood, little is known regarding how Abl promotes progression of solid tumors.…”
Section: Introductionmentioning
confidence: 99%